Pengaruh Pelatihan dan Lingkungan Kerja terhadap Komitmen Pegawai pada Pusat Pelayanan Panti Sosial Meci Angi Kota Bima - Eti Sumiyati; Firmansyah Kusumayadi; Khairul Ammar (Lembaga Pendidikan dan Penelitian Manggala Institute, 2026)
This study aims to analyze the influence of training and the work environment on employee commitment at the Meci Angi Social Welfare Service Center in Bima City. Employee commitment is a crucial factor determining an organization's success in achieving its goals. Enhancing employee commitment can be influenced by various factors, including effective training and a conducive work environment. Therefore, this study was conducted to determine the impact of training and the work environment—both individually and simultaneously—on employee commitment. This study employs a quantitative approach with an associative research design. The population consists of all employees at the Meci Angi Social Welfare Service Center in Bima City. A saturated sampling technique (census) was used, meaning all employees served as research respondents. Data collection was carried out by distributing questionnaires using a Likert scale. Data analysis techniques included validity testing, reliability testing, classical assumption testing, multiple linear regression analysis, t-tests (partial), F-tests (simultaneous), and the coefficient of determination (R²).